Handbook of Adolescent Psychology (Vol.I) : Individual Bases of Adolescent Development - Lerner, Richard M. and Steinberg, Laurence., 1952- (Hoboken John Wiley & Sons, 2009)
The study of and interest in adolescence in the field of psychology and related fields continues to grow, necessitating an expanded revision of this seminal work.
Include Index
Keywords: Adolescent psychology